Self-Perception of Critical Thinking in High School Students Through Scientific Inquiry on DNA Extraction - Arana-Cuenca, Ainhoa; Morcillo de Amuedo, Fernando; Garrido Álvarez-Coto, Guiomar (Educational Process: International Journal, 2025)
Background/purpose. Practical work is a key component of science education that can contribute to comprehensive learning and scientific literacy. This study presents the results of an Inquiry-Based Learning (IBL) approach using a DNA extraction practice with 4th-year secondary education Spanish students. The findings highlight significant improvements in knowledge acquisition and self-perception of critical thinking. Students reported high satisfaction and increased interest in science. This study addresses the issue of declining interest and curiosity towards science among students. The purpose is to evaluate the impact of an Inquiry-Based Learning strategy, centered on DNA extraction, on the development of self-perception of critical thinking and scientific knowledge among high school students. Materials/methods. The study utilized a pre-experimental design with pre-test and post-test measures. It included 25 students who designed and conducted their own experiments on DNA extraction, followed by writing a scientific article. Instruments included questionnaires assessing knowledge, self-perception of critical thinking, and student satisfaction. Results. The intervention led to significant improvements in knowledge scores (mean increase from 6.0 to 7.1) and self-perception of critical thinking, particularly in evaluating specific situations with objective and subjective data. Satisfaction levels were high, with students appreciating the hands-on and innovative approach. Conclusion. The implementation of an Inquiry-Based Learning approach using DNA extraction improved students’ knowledge and self-perception of critical thinking, particularly in evaluating situations with data. The high level of satisfaction indicates the potential of such strategies to enhance interest in science and promote scientific literacy.
Keywords: Scopus; inquiry-based learning; DNA extraction; critical thinking; science education; self-perception